2010
DOI: 10.5539/ibr.v4n1p51
|View full text |Cite
|
Sign up to set email alerts
|

The separation of ownership and control and investment decisions in Mexican manufacturing firms

Abstract: We study how the ownership and control structures may explain investment decisions of Mexican manufacturing firms. We study them with aggregate indexes and the assessment of several regression sets. We use measures of ownership, management and agency costs. The econometric analysis uses longitudinal census data for 182 industries. Our findings support the claim that agency costs, as a measure of the separation of management and control, and firms` size can explain investment decisions. Furthermore the estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
4
10
0
Order By: Relevance
“…Many scholars have emphasize investigating direct relationships between product competition and its impact on firm performance. Some of them provides positive relationships ( Ruiz-Porras and Lopez-Mateo, 2011 ; Van Reenen, 2011 ; Javeed et al, 2020 ), while others negative or U shape ( Januszewski et al, 2002 ; Bloom et al, 2010 ; Ko et al, 2016 ). These studies did not clarify how product market competition can be associated with firm performance positively, negatively, or neutrally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars have emphasize investigating direct relationships between product competition and its impact on firm performance. Some of them provides positive relationships ( Ruiz-Porras and Lopez-Mateo, 2011 ; Van Reenen, 2011 ; Javeed et al, 2020 ), while others negative or U shape ( Januszewski et al, 2002 ; Bloom et al, 2010 ; Ko et al, 2016 ). These studies did not clarify how product market competition can be associated with firm performance positively, negatively, or neutrally.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has shown that product competitiveness provides a positive impact, while some studies identify a negative relation to better firm performance. The findings of empirical studies indicated that product competition leads to achieving better performance and higher profits because firms’ competitiveness resolves agency conflicts between stakeholders, owners, and managers, which results in better profitability of the firms ( Raith, 2003 ; Ruiz-Porras and Lopez-Mateo, 2011 ; Mubeen et al, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many scholars have explored the direct relationship between product market competition and firm performance. Some positive relationships were found ( Ruiz-Porras and Lopez-Mateo, 2011 ; Van Reenen, 2011 ; Javeed et al, 2020 ), while others were negative or U shape ( Januszewski et al, 2002 ; Bloom et al, 2010 ; Ko et al, 2016 ). Thus, the literature did not explain the negative, positive, or neutral relationship between product market competition and firm performance.…”
Section: Discussionmentioning
confidence: 97%
“…According to Ruiz-Porras and Lopez-Mateo (2011), corporate governance theory contributes to explaining firms’ behaviour and their decisions, like investment ones. Gill et al (2012) also posit that good corporate governance is necessary for firms to make sound investment decisions which, in turn, help firms to prosper in the domestic as well as in the global market.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%